An Analysis of Gender Gap in Access to Extension Services - Manoshi Baruah Deka, Pompi Saikia2and Rekha Moni Saikia (Indian Journal of Extension Education, 2018)
Women produce between 60 -80 percent of food in most developing countries and are responsible for half of the world’s food production with fewer resources, less access to technology and the added responsibility of child and family but they receive little or no support from mainstream agricultural extension services. This paper reports information on gender differentials in access to extension services in the state of Assam . Using a cross-sectional study design, data was collected from a random sample of 1100 farm families. In majority (53.20 %) of the households, men owned land compared to 31.5 per cent and 15.3 per cent that was either jointly owned or by women. Both rural women and men included as respondents in the present study possessed knowledge of different extension personnel, Access to extension information was dominated by 47.5 per cent of the men while only 32.5 per cent of the women had access. Reasons given for non participation was that the shortage of time for both rural women and men (58.23 %) ,sometimes it was because organising without prior notice (48.11 %) and also venue and time not suitable to participate. However, there is a gender bias on the part of the institutions providing extension services. Findings show that despite the women’s important role in agricultural production, disparities exist in the receiving extension services and training programmes in the province. Factors shaping the gender gap were found to be due to notions about who is a farmer and narrow definition of women’s roles in agriculture, targeting rural women as extension clients and targeting male extension agents. It is strongly recommended to train men extension agents in culturally acceptable methods of delivering extension services to women along with alternate extension methodologies such as ICTs.